| library test /*isNonNullableByDefault*/; |
| import self as self; |
| import "dart:core" as core; |
| |
| class A extends core::Object { |
| synthetic constructor •() → self::A |
| : super core::Object::•() |
| ; |
| } |
| class B extends self::A { |
| synthetic constructor •() → self::B |
| : super self::A::•() |
| ; |
| operator +(self::C v) → self::B |
| return throw ""; |
| operator -(core::int i) → self::B |
| return throw ""; |
| operator *(self::B v) → self::B |
| return throw ""; |
| operator &(self::A v) → self::C |
| return throw ""; |
| } |
| class C extends self::B { |
| synthetic constructor •() → self::C |
| : super self::B::•() |
| ; |
| } |
| class Base extends core::Object { |
| field self::B member; |
| field self::B? member2 = null; |
| constructor •(self::B member) → self::Base |
| : self::Base::member = member, super core::Object::•() |
| ; |
| } |
| class Test extends self::Base { |
| constructor •(self::B member) → self::Test |
| : super self::Base::•(member) |
| ; |
| method test() → void { |
| super.{self::Base::member} = self::f<self::B>(); |
| super.{self::Base::member2} == null ?{self::B?} super.{self::Base::member2} = self::f<self::B?>() : null; |
| super.{self::Base::member} = super.{self::Base::member}.{self::B::+}(self::f<self::C>()){(self::C) → self::B}; |
| super.{self::Base::member} = super.{self::Base::member}.{self::B::*}(self::f<self::B>()){(self::B) → self::B}; |
| super.{self::Base::member} = super.{self::Base::member}.{self::B::&}(self::f<self::A>()){(self::A) → self::C}; |
| super.{self::Base::member} = super.{self::Base::member}.{self::B::-}(1){(core::int) → self::B}; |
| super.{self::Base::member} = super.{self::Base::member}.{self::B::-}(1){(core::int) → self::B}; |
| self::B v1 = super.{self::Base::member} = self::f<self::B>(); |
| self::B? v2 = let final self::B? #t1 = super.{self::Base::member2} in #t1 == null ?{self::B?} super.{self::Base::member2} = self::f<self::B?>() : #t1{self::B}; |
| self::B v3 = super.{self::Base::member} = super.{self::Base::member}.{self::B::+}(self::f<self::C>()){(self::C) → self::B}; |
| self::B v4 = super.{self::Base::member} = super.{self::Base::member}.{self::B::*}(self::f<self::B>()){(self::B) → self::B}; |
| self::C v5 = super.{self::Base::member} = super.{self::Base::member}.{self::B::&}(self::f<self::A>()){(self::A) → self::C}; |
| self::B v6 = super.{self::Base::member} = super.{self::Base::member}.{self::B::-}(1){(core::int) → self::B}; |
| self::B v7 = let final self::B #t2 = super.{self::Base::member} in let final self::B #t3 = super.{self::Base::member} = #t2.{self::B::-}(1){(core::int) → self::B} in #t2; |
| } |
| } |
| static method f<T extends core::Object? = dynamic>() → self::f::T% |
| return throw ""; |
| static method main() → dynamic {} |